Modification on drying chamber wall of spray dryer towards better yield - Nik Farhan Nazmi Nik Abd Rahman,; Haslaniza Hashim,; Saiful Irwan Zubairi,; Mohamad Yusof Maskat, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Spray drying is a widely used industrial process that converts liquid or slurry feed materials into dry powder or granules and it commonly shrouded with the stickiness problem. This study was carried out by response surface methodology (RSM) to minimize fouling during the spray drying process by optimizing the condition of the drying chamber wall of the spray dryer. The concentration (%) and exposure time (min) of polytetrafluoroethylene (PTFE) were examined as independent variables in order to modify the dryer wall. Responses including flux adhesion weight, product recovery, hygroscopicity, and moisture content of the powder were evaluated. Statistical analysis showed that experimental data were best fitted into a quadratic polynomial model with regression coefficient values greater than 0.75 for all responses. The optimum conditions in reducing fouling were discovered at PTFE concentration of 17.27% and PTFE exposure time of 6 min. These conditions would result in low flux adhesion weight (35.28 mg), high product recovery (39.38%), low hygroscopicity (6.08%) and low moisture content (7.97%). The observed outcomes aligned with the predicted values, affirming the suitability of the model in improving the flowability of the spray drying process.